44 A review of glycoprotein IIB/IIIA inhibitors in primary PCI within the belfast HSC trust - Thompson, P; Campbell, M; McNeice, A (Heart (British Cardiac Society), 2023)
IntroductionThere is no clear consensus within the guidelines identifying when Glycoprotein IIb/IIIa inhibitors (GPI) should be used in the setting of Primary PCI (PPCI). The ESC have removed their 2012 recommendation for routine use of GPI in patients without contraindications and now state that GPI should be considered as bailout in no reflow or thrombotic complications. Likewise NICE recommend GPI as a bailout strategy in patients with acute STEMI and radial access. Across the UK there has been a significant reduction in the use of GPI between 2005 and 2020. This corresponds with the introduction of routine Dual Antiplatelet Therapy and a move toward novel P2Y12 inhibitors. Despite this there is still wide variation between PPCI centres within the UK and no clear consensus on the optimal use of GPI.AimsWe aim to quantify the use of GPI during PPCI in a large volume UK Primary PCI centre with onsite cardiothoracic surgery and record the rates of all-cause mortality, bleeding and ischaemic complications.MethodsData was collected retrospectively from the National Electronic Care Record of consecutive patients presenting via the PPCI pathway between 1/4/2021 – 31/3/2022. Complications were recorded following review via an adjudication committee. Bleeding complications were defined using PLATO Major Bleeding criteria. Patients who did not undergo invasive coronary angiography, received no intervention or did not have follow-up data were excluded (table 1).ResultsAbstract 44 Table 1Patient demographicsThere were 857 PPCI activations; 715 subjects were included and GPI were used in 55.9% of cases. There was no statistical differences in mortality outcomes at 30 days: GPI 6.3% (4.2–9.8%) vs control 7.3% (4.8–10.6%) p=0.6. With regard to stent thrombosis and target vessel revascularisation there was a numeric signal towards fewer events in the GPI group at 30 days. Stent thrombosis: GPI 0.5% (0.1–1.6%) vs control 1.0% (0.3–2.5%) p=0.47. Target Vessel revascularisation: GPI 0.8% (0.2–2.0%) vs control 2.2% (1.0–4.4%) p=0.10. There was no significant difference between both groups in bleeding outcomes at 30 days: GPI 1.0% (0.3–2.4%) vs control 1.6% (0.6–3.5%) P=0.49 or vascular complications: GPI 0.8% (0.2–2.0%) vs control 0.3% (0.0–1.5%) p=0.44 (figure 1).Abstract 44 Figure 1Summary of key factors to aid decision making[Figure omitted. See PDF]ConclusionIn this large volume PPCI centre over half of cases received GPI. There was no statistically significant difference in mortality, thrombotic or bleeding complications between those that received GPI and those that did not. Consideration should be given to the bleeding and ischaemic risk of patients when determining whether to administer GPIs.